Handbook of Artificial Intelligence and Robotic Process Automation Policy and Government Applications - Naqvi, Al; Naqvi, Al; Munoz, J. Mark (Anthem Press, 2020)
President Putin$1 (Bs explicit declaration that the country that makes progress in artificial intelligence will rule the world has launched a new race for dominance. In this era of cognitive competition and total automation, every country understands that it must rapidly adopt AI or go bust. To stay competitive a country must have a strategy. But how should a government proceed? What areas it must focus on? Where should it even start? This book provides answers to these important, yet pertinent, questions and more. Presenting the viewpoints of global experts and thought leaders on key issues relating to AI and government policies, this book directs us to the futures